Practical Guide to the Assessment of the Useful Life of Rubbers - Brown, R.P. (Rapra Technology Limited, 2011)
The object of this publication is to provide practical guidance on assessing the useful service life of plastics. It describes test procedures and extrapolation techniques together with the inherent limitations and problems.